DESAIN STANDAR AKUNTANSI KARBON DAN MODEL INTEGRASI PELAPORAN EMISI KARBON DALAM LAPORAN KEUANGAN - Purwanti, Titik; Setyawanti, Dandang; Jati, Agung Nugroho (KIAT BISNIS, 2013)
DESAIN STANDAR AKUNTANSI KARBON DAN MODEL INTEGRASI PELAPORANEMISI KARBON DALAM LAPORAN KEUANGANTitik PurwantiFakultas Ekonomi Universitas Widya Dharmatitik@unwidha.ac.idDandang SetyawantiFakultas Ekonomi Universitas Widya Dharmadandang@unwidha.ac.idAgung Nugroho JatiFakultas Ekonomi Universitas Widya Dharmaagung@unwidha.ac.idAbstractThis research aims to test empirically The Effect of Carbon Accounting Standards, FinancialControl System, Sales Management, Guarantee of Corporate Governance and the Carbon FactorAudit affect the Accounting Paradigm. Population of this research is manufacturing company atJawa Tengah. Sampel penelitian diambil dari populasi dengan teknik purposive random sampling.Sampling method uses purposive sampling method. Data analysis technique uses classicassumptions test: multicolinierity test, autocorrelation test, heteroscedasticity test and normalitytest. Hypothesis test uses multiple regression analysis. The conclution of this research are: CarbonAccounting Standards decisions positively affects the Accounting Paradigm value regressioncoefficient is 0,000 and level significance is of 0,05, Financial Control System decisions positivelyaffects the Accounting Paradigm value regression coefficient is 0,000 and level significance is of0,05, Sales Management decisions positively affects the Accounting Paradigm value regressioncoefficient is 0,009 and level significance is of 0,05, guarantee of Corporate Governance positivelyaffects the Accounting Paradigm value regression coefficient is 0,014 and level significance is of0,05, the Carbon Factor Audit decisions positively affects the Accounting Paradigm valueregression coefficient is 0,007 and level significance is of 0,005.Keywords: Effect of Carbon Accounting Standards, Financial Control System, SalesManagement, Guarantee of Corporate Governance, Carbon Factor Audit